Dying to starve: a comparative analysis of legal aspects relating to consent in force-feeding of both minor and adult anorexic patients - Karels, M. G.; Oosthuizen, H. (Faculty of Law, University of the Free State, 2010)
The authors explore the legal complexities surrounding the force-feeding of anorexic patients. Due to the myriad of difficulties relating to anorexia nervosa, treatment is intricate. The aim of this exposition is to clarify legal issues of consent and self-determination, with regard to both adult and minor patients. In addition, the distinction between 'irrational' and 'incompetent' refusal will be discussed, with the authors maintaining that the 'irrational' refusal of an adult patient should be respected by the law. To come to an informed conclusion, the authors will first analyse the medical and psychological aspects of anorexia nervosa. Secondly, the South African position as shaped by the Mental Health Care Act, the Children's Act and the National Health Act will be contrasted with the position in Great Britain in order to determine the international perspective and its contrast, or not, to South African law.

Die outeurs ondersoek hoe ingewikkeld die wetlike aspekte van gedwonge voeding van anoreksiese pasiente is. Die problematiek rondom anorexia nervosa bemoeilik die behandeling daarvan. Die oogmerk van hierdie bespreking is om helderheid te bied ten opsigte van die regsaspekte van toestemming en selfbeskikking by kinders en volwasse pasiente. Voorts sal die verskil tussen irrasionele en onbevoegde weiering van toestemming tot behandeling bespreek word. Die outeurs is van mening dat irrasionele weiering deur 'n volwassene deur die reg gerespekteer moet word. Ten einde 'n ingeligte gevolgtrekking te kan maak, sal die outeurs eerstens die geneeskundige en psigologiese aspekte van anorexia nervosa, ontleed. Bykomend daartoe sal die Mental Health Care Act, die Childrens' Act en die National Health Act van Suid-Afrika vergelyk word met soortgelyke wetgewing in Groot-Brittanje om internasionale perspektiewe te bepaal.